Sukarno, tentara, PKI segitiga kekuasaan sebelum prahara politik, 1961-1965 - Anwar, Rosihan 1922-2011 (Yayasan Obor, 2007)
Power play among Soekarno, Indonesia's first president, Angkatan Bersenjata (the Indonesian Armed Forces), and Partai Komunis Indonesia (The Indonesian Communist Party) just before the 1965 Coup d'etat.